2014
DOI: 10.1101/007807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanding xylose metabolism in yeast for plant cell wall conversion to biofuels

Abstract: Sustainable biofuel production from renewable biomass will require the efficient and complete use of all abundant sugars in the plant cell wall. Using the cellulolytic fungus Neurospora crassa as a model, we identified a xylodextrin transport and consumption pathway required for its growth on hemicellulose. Reconstitution of this xylodextrin utilization pathway in Saccharomyces cerevisiae revealed that fungal xylose reductases act as xylodextrin reductases, producing xylosyl-xylitol oligomers as metabolic inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…It is worth noting that the XR/XDH pathway has been shown to produce much less xylitol or no xylitol when xylodextrins are used rather than xylose in fermentations [13], or when undetoxified lignocellulose hydrolysate is used [6]. Thus, xylodextrin consumption by means of the XR/XDH pathway could result in yeast strains with both high ethanol productivity and yield, without the drawback of xylitol byproduct formation.…”
mentioning
confidence: 99%
“…It is worth noting that the XR/XDH pathway has been shown to produce much less xylitol or no xylitol when xylodextrins are used rather than xylose in fermentations [13], or when undetoxified lignocellulose hydrolysate is used [6]. Thus, xylodextrin consumption by means of the XR/XDH pathway could result in yeast strains with both high ethanol productivity and yield, without the drawback of xylitol byproduct formation.…”
mentioning
confidence: 99%
“…which has led to many efforts to relieve this inhibition [21,22]. We had previously observed that cellobiose inhibits xylobiose transport by CDT-2 [7]. We therefore tested xylobiose transport activity in the presence of increasing molar concentrations of cellobiose, up to 10 times the concentration of X2.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore chose ST16, which is derived from Trichoderma virens, as the starting point for setting up a directed evolution experiment to improve XD consumption. Based on experiments published previously, in which XD consumption was rapidly turned on and off in anaerobic conditions [7], we hypothesized that XD transport is limiting in terms of consumption rate. Notably, when we inserted the transporter ST16 under control of PGK1 promoter and TPS3 terminator into the yeast genome at the LEU2 locus, there was a dramatic decrease in the growth rate compared with overexpression ST16 from a plasmid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations